Respuesta :
Assuming you mean the sequence is given explicitly by [tex]a_n=2n+5[/tex], the sum of the first 15 terms is
[tex]\displaystyle\sum_{n=1}^{15}a_n=\sum_{n=1}^{15}(2n+5)=2\sum_{n=1}^{15}n+5\sum_{n=1}^{15}1[/tex]
Recall Faulhaber's formulas, which say
[tex]\displaystyle\sum_{n=1}^k1=k[/tex]
[tex]\displaystyle\sum_{n=1}^kn=\dfrac{k(k+1)}2[/tex]
Our sum is then
[tex]\displaystyle\sum_{n=1}^{15}a_n=2\dfrac{15\times16}2+5\times15=315[/tex]
[tex]\displaystyle\sum_{n=1}^{15}a_n=\sum_{n=1}^{15}(2n+5)=2\sum_{n=1}^{15}n+5\sum_{n=1}^{15}1[/tex]
Recall Faulhaber's formulas, which say
[tex]\displaystyle\sum_{n=1}^k1=k[/tex]
[tex]\displaystyle\sum_{n=1}^kn=\dfrac{k(k+1)}2[/tex]
Our sum is then
[tex]\displaystyle\sum_{n=1}^{15}a_n=2\dfrac{15\times16}2+5\times15=315[/tex]
Answer:
[tex]\sum _{n=1}^{15}2n+\sum _{n=1}^{15}5=240+75=315[/tex]
Step-by-step explanation:
Given: [tex]\sum _{n=1}^{15}\:2n+5[/tex]
We have to calculate the sum of given expression.
Consider the given expression [tex]\sum _{n=1}^{15}\:2n+5[/tex]
Apply sum rule,[tex]\sum a_n+b_n=\sum a_n+\sum b_n[/tex] , we get,
[tex]=\sum _{n=1}^{15}2n+\sum _{n=1}^{15}5[/tex]
Now first consider [tex]\sum _{n=1}^{15}2n[/tex]
Using constant multiplication rule, [tex]\sum c\cdot a_n=c\cdot \sum a_n[/tex]
we have,
[tex]=2\cdot \sum \:_{n=1}^{15}n[/tex]
Apply sum formula, [tex]\sum _{k=1}^nk=\frac{1}{2}n\left(n+1\right)[/tex]
[tex]=\frac{1}{2}\cdot \:15\left(15+1\right)=120\\\\ \sum _{n=1}^{15}2n=240[/tex]
Now consider [tex]\sum _{n=1}^{15}5[/tex]
Apply sum formula, [tex]\sum _{k=1}^n\:a\:=\:a\cdot n[/tex]
Here, a = 5 and n = 15
we get [tex]\sum _{n=1}^{15}5=75[/tex]
Therefore [tex]\sum _{n=1}^{15}2n+\sum _{n=1}^{15}5=240+75=315[/tex]